(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we initiate the study on zero forcing domination in a graph and we characterize the zero forcing dominating sets in some special graphs and the join of two graphs. We derive some formulas of the parameter using characterization results. Moreover, we present some relationships of this parameter with other known parameters in graph theory.